Kidney Tubules — Scientific and Applied Value - E. s Levitskaya; M. M. Batiushin (Архивъ внутренней медицины, 2022)
Currently, there is a high scientific interest in studying the features of the structure and functions of the tubules of the kidneys. The relevance of the topic is due to the potential possibility of identifying various markers of tubular dysfunction and using them for early diagnosis of not only tubulopathies, but also glomerular disorders. In clinical practice, markers of tubular dysfunction are used insufficiently. The article presents information about the anatomical and functional features of the proximal and distal parts of the tubular apparatus, outlines highly organized mechanisms of intermolecular interaction, presents the main biologically active substances, the change in the concentration of which is a consequence of damage to the tubules. The presented manuscript is the product of a deep analysis and systematization of the available data in Russian and foreign information and analytical portals.